Litter Productivity of Dry Deciduous Teak Forest Stands of Sagar (Madhya Pradesh) - Prasad, Ram; Mishra, G. P. (Indian Forester, 1985)
Studies on the litter productivity of a natural dry deciduous teak forests of Sagar (Madhya Pradesh) have been reported in this investigation. It has been observed that T. grandis alone produced one-third of the total production of stand. The other species which dominated the litter output in stand were : T. tomentosa, D. melanoxylon, Butea monosperma and Miliusa tomentosa. Small broken pieces of minor species accounted for another one-third of the total production. Other important tree species such as A. latifolia and L. parviflora in spite of their high plant density contributed only a fraction of the tota1 litter production indicating the immature plant stand of these species. The total leaf litter production in these forests was found to be 4.959 tonnes/ha. In the light of present investigations, it can be concluded that while relatively younger crop is more efficient in litter production, their distribution pattern is most important. Abundence of plants in juvenile phase instead of seedling and coppice phase appears to produce maximum foliage. Once the trees cross the juvenile phase the canopy is closed and thus the size of crown remains constant. It was not due to bigger crown and more leaves but due to thicker branch wood. Besides age, the tree density and basal area play equally significant role in leaf litter output. This hypothesis can be explained by the basal area and litter output of T. grandis and T. tomentosa. In addition to remaining dead parts of the above ground vegetation, leaf litter considerably adds to the forest floor. Herbaceous ground flora also enrich the forest floor with organic matter both directly and indirectly. It traps around its litters and stumps a large quantity of leaf litter which would have otherwise gone out side of the ecosystem.